UMP seals MOU with Pasdec, Hicom to cooperate on academic, research, human capital development - UMP, PNC
Universiti Malaysia Pahang (UMP) sealed a Memorandum of Understanding (MOU) with Pasdec Holdings Bhd and Hicom Automotive Manufacturers Sdn Bhd at a signing ceremony during the official opening of the East Coast National Higher Education Carnival at the Chancellery Square on February 28 last year.